Rotational Thromboelastometry in High-Risk Patients on Dual Antithrombotic Therapy After Percutaneous Coronary Intervention - Hulshof, Anne-Marije; Olie, Renske H.; Vries, Minka J. A.; Verhezen, Paul W. M.; van der Meijden, Paola E. J.; ten Cate, Hugo; Henskens, Yvonne M. C. (Frontiers in Cardiovascular Medicine, 2021)
Aims: Patients using antithrombotic drugs after percutaneous coronary intervention (PCI) are at risk for bleeding and recurrent ischemia. We aimed to explore routine and tissue plasminogen activated (tPA) ROTEM results in a post-PCI population on dual antithrombotic treatment. Methods and results: In this prospective cohort, 440 patients treated with double antithrombotic therapy after recent PCI and with ≥3 risk factors for either ischemic or bleeding complications were included and compared with a control group (n=95) consisting of perioperative patients not using antithrombotic medication. Laboratory assessment, including (tPA) ROTEM, was performed one month post-PCI and bleeding/ischemic complications were collected over a five-month follow-up. Patients were stratified by antithrombotic regimen consisting of a P2Y12 inhibitor with either aspirin (dual antiplatelet therapy; DAPT, n=323), a vitamin K antagonist (VKA, n=69) or a direct oral anticoagulant (DOAC, n=48). All post-PCI patients had elevated ROTEM clot stiffness values, but only the DAPT group additionally presented with a decreased fibrinolytic potential as measured with tPA ROTEM. Patients receiving anticoagulants had prolonged clotting times (CT) when compared to the control and DAPT group; EXTEM and FIBTEM CT could best discriminate between patients (not) using anticoagulants (AUC>0.97). Furthermore, EXTEM CT was significantly prolonged in DAPT patients with bleeding complications during follow-up (68 [62-70] vs 62 [57-68], p=0.030). Conclusion: ROTEM CT has high potential for identifying anticoagulants and tPA ROTEM could detect a diminished fibrinolytic potential in patients using DAPT. Furthermore, the ability of EXTEM CT to identify patients at risk for bleeding may be promising and warrants further research.